Sociological Culture and Civilization - دلالة ميرنا أحمد; الشيخ عفراء مسعود (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research studies the concept of sociological culture and not culture in its general sense. It, first of all, discusses the notion of culture and its types in an attempt to uncover the semiotic variance of culture in the domain of sociological studies. So, it tackles and differentiates between the five types of culture, and it reveals the demarcations between each cultural type. After that, the research studies, by necessity, the sociological categorization of culture by sociologists, in general, and by Durkheim in particular. It also approaches the latter’s mechanics of classification upon which he hinges in studying sociological culture. The research then moves to tackle the dialectical relation between culture and civilization. The sociological origin of culture is thus expounded. The dialectical relation between the material and spiritual components of civilization and generally between the individual, society and civilization is revealed as well.